Improving Parkinson’s disease management through wearable technology: A cost-benefit perspective - Daniel Rodriguez-Martin; Andreu Català; Joan Cabestany (PLoS ONE, 2025)
Parkinson’s Disease (PD) is a progressive neurodegenerative disorder affecting millions of patients worldwide, with significant economic and social implications. The increasing prevalence of PD, coupled with rising healthcare costs, necessitates cost-effective solutions for patient management. Wearable medical devices, such as STAT-ON™, an inertial sensor with AI processing capability, offer an opportunity to enhance symptom monitoring, optimize therapy adjustments, and improve patient quality of life (QoL). However, their cost-effectiveness in routine clinical practice remains insufficiently explored. This study conducts a cost-benefit analysis of integrating STAT-ON™ into European healthcare systems (Spain, Sweden, Germany, Italy, and the UK). Using validated clinical data, we assess the economic impact of early symptom detection facilitated by continuous monitoring. Our findings suggest that improved symptom assessment can lead to optimized medication regimens, reducing hospitalizations and institutional care costs. While medication costs may increase, overall direct healthcare expenses decrease, leading to net savings. As an example, the study estimates potential cost reductions of up to €137.8 million in Germany and €19 million in Sweden when STAT-ON™ is used to detect advanced PD symptoms. Despite these promising results, limitations exist, including variations in healthcare costs, reimbursement policies, and real-world adoption rates across the different countries. Additionally, indirect costs such as caregiver burden were not fully analyzed. Future longitudinal studies are needed to further validate the economic and clinical benefits of wearable monitoring devices in PD management. This study highlights the potential of STAT-ON™ as a valuable tool for reducing healthcare costs and enhancing patient outcomes, supporting its adoption as a complementary solution for objective PD assessment in clinical practice.